If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 5 = -2x + 19 Reorder the terms: 5 + 12x = -2x + 19 Reorder the terms: 5 + 12x = 19 + -2x Solving 5 + 12x = 19 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 5 + 12x + 2x = 19 + -2x + 2x Combine like terms: 12x + 2x = 14x 5 + 14x = 19 + -2x + 2x Combine like terms: -2x + 2x = 0 5 + 14x = 19 + 0 5 + 14x = 19 Add '-5' to each side of the equation. 5 + -5 + 14x = 19 + -5 Combine like terms: 5 + -5 = 0 0 + 14x = 19 + -5 14x = 19 + -5 Combine like terms: 19 + -5 = 14 14x = 14 Divide each side by '14'. x = 1 Simplifying x = 1
| .09x=10 | | 2/9v=14 | | .09x=15 | | -x^3+1.5x^2-.5x=0 | | -x^3+1.5x^2-04x=0 | | 3+10=5 | | A=(1/2)bb | | 2cos^2(x)+9cos(x)=0 | | 3y+8=2y-8 | | -3x+9=3+4x+(-7x)+6 | | 4y=y+35 | | 4000*4.254= | | B/3=-27 | | M-1/6=5/6 | | -6(8x+15)=390 | | -10+-8m=-110+6m | | g(x)=-6x-7 | | -7(6x+2)=-266 | | 7x+2=5x+(-2) | | 6(-9x+5)=-240 | | 7(x)-2=26 | | -6(-6x-10)=276 | | -16+4x=5(x-1) | | 16n^2+8n+1= | | x^4-3x^3+4x^2-7x+15=0 | | 7-7n+3n=11-92 | | -6x-2=12 | | -9(6x-16)=468 | | 5(-10x-13)=-415 | | ln(x-1)=2.3 | | 6(9x+17)=426 | | 0=3t^2-2t |